Literatura paraguaya: un grito en voz baja - Bernardo NERI FARINA (Caravelle)
Paraguay has a literature of its own still searching to achieve a specific voice and, above all, which hasn’t found yet a response from a society that would take hold of it. There is a kind of determinism which has delayed for a long time the emergence of mature literary manifestations, in a medium that despised fiction because they wanted writings about “realities”, though Paraguayan reality often goes beyond the most delirious fiction. This article gives a panoramic view of Paraguayan literature and its relation with history’s influence as well as its actual production, overcoming obstacles such as: an educational system which doesn’t develop reading and the lack of public politics that promote culture and literary production.